ZnO Nanorods: Synthesis by Catalyst-Free CVD and Thermal Growth from Salt Composites and Application to Nanodevices - Kononenko, Oleg V.; Redkin, Arkady N.; Baranov, Andrey N.; Panin, Gennady N.; Kovalenko, Artem A.; Firsov, Anatoly A. (IntechOpen, 2012)
None